Immune Pathogenesis of Asymptomatic Chlamydia trachomatis Infections in the Female Genital Tract - Steven S. Witkin (Hindawi Limited, 1995)
Chlamydia trachomatis (CT) infections of the female genital tract, although frequently asymptomatic, are a major cause of fallopian-tube occlusion and infertility. Early stage pregnancy loss may also be due to an unsuspected and undetected CT infection. In vitro and in vivo studies have demonstrated that this organism can persist in the female genital tract in a form undetectable by culture. The mechanism of tubal damage as well as the rejection of an embryo may involve an initial immune sensitization to the CT 60 kD heat shock protein (HSP), followed by a reactivation of HSP-sensitized lymphocytes in response to the human HSP and the subsequent release of inflammatory cytokines. The periodic induction of human HSP expression by various microorganisms or by noninfectious mechanisms in the fallopian tubes of women sensitized to the CT HSP may eventually result in tubal scarring and occlusion. Similarly, an immune response to human HSP expression during the early stages of pregnancy may interfere with the immune regulatory mechanisms required for the maintenance of a semiallogeneic embryo.